2021
DOI: 10.1039/d1nr02765d
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the mechanism of small size effect in carbon-based supercapacitors

Abstract: Small size effect could be conducive to enhancing the electrochemical performance, while the mechanism by which they also increase the capacitance for carbon electrode materials has not been established. Here,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Yang et al 82 The diaza-cage monomer, ADBr, 8 (1-(2-acryloyoxyethyl)azonium-4-aza-bicyclo[2.2.2]octane bromide), was derived from 2-bromoethyl acrylate and DABCO (diazabicyclo[2.2.2]octane), developed for use in forming mesoporous supports for iron oxide nanoparticles 84 and polyacrylonitrile nanoparticles 85 for catalytic and supercapacitor applications, respectively. The diaza-cage, 1,4-diazabicyclo[2.2.2]octane (triethylenediamine), was quaternized by reacting with 2-bromoethyl acrylate.…”
Section: Vinyl Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al 82 The diaza-cage monomer, ADBr, 8 (1-(2-acryloyoxyethyl)azonium-4-aza-bicyclo[2.2.2]octane bromide), was derived from 2-bromoethyl acrylate and DABCO (diazabicyclo[2.2.2]octane), developed for use in forming mesoporous supports for iron oxide nanoparticles 84 and polyacrylonitrile nanoparticles 85 for catalytic and supercapacitor applications, respectively. The diaza-cage, 1,4-diazabicyclo[2.2.2]octane (triethylenediamine), was quaternized by reacting with 2-bromoethyl acrylate.…”
Section: Vinyl Monomersmentioning
confidence: 99%
“…616 The PILderived core−shell structure displayed remarkable catalytic activity and high selectivity in self-dehydrogenation and Apart from PILderived carbon-based catalysts, a number of carbon materials with special structures originating from PIL precursors were used as efficient electrodes in supercapacitors and batteries. 85,420,742 Josef et al reported a conductive carbon fiber that can replace metal as a collector in supercapacitors, as shown in Figure 48. 743 The synthesized PIL and 5 wt % PVP were mixed and then electrospun in an organic acid crosslinked solution to preserve the fiber structure.…”
Section: Pil Derivativesmentioning
confidence: 99%
“…Experiments and atomic simulations have proven that when the material structure size decreases to the micro/nano scale, the impact of small size cannot be ignored [5,6]. However, as the size decreases, the material will exhibit scale effects [7].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon, transition metal oxides and conducting polymer-based nanomaterials have been widely utilised as electrode active substances for SC's applications. However, carbon is still the most deployed active material in commercially used supercapacitor devices since using conducting polymers and transition metal oxide-based nanomaterials can result in inferior power densities of SC devices, which is the fundamental advantage for the preferred use of SCs in many high-power delivery applications [11,12]. Carbonbased materials are commonly used in SCs because of their excellent physical, chemical, and electrochemical characteristics including very high surface area, control over porous structures, good electrical conductivities, chemical inertness, structural stability, control of functionalisation, and flexibility of producing a wide range of composites [13,14].…”
Section: Introductionmentioning
confidence: 99%